Potret Kepemimpinan Perempuan pada Lurah Mangunharjo, Kecamatan Tembalang, Kota Semarang - Siti Nabilla Hanum; Dyah Hariani; Augustin Rina Herawati (Journal of Public Policy and Management Review, 2021)
The dominance of male village chief in Semarang City is not a challenge for Mangunharjo village chief as a female leader. On the other hand, the village chief of Mangunharjo showed a good performance and even brought changes to the Mangunharjo area. It has been proven that under the leadership of the village chief since 2012, Mangunharjo has won many competitions. This research was conducted to describe and analyze the leadership style applied by female village chief in Mangunharjo Village and to analyze the driving factors of the success of their leadership. The approach used is descriptive qualitative. Data were collected from interviews with the village head, village officials, village partners, and the community, as well as supporting documents. The research findings indicate that the leadership of the Mangunharjo village head tends to practice a transformational leadership style. The factors that support the success of the Mangunharjo village head include a sense of belonging from subordinates, openness to suggestions and input, community involvement, and support from various parties.